Impact of Acute Kidney Injury on Critically Ill Children and Neonates - Leghrouz, Bassil; Kaddourah, Ahmad (Frontiers in Pediatrics, 2021)
Acute Kidney Injury (AKI) is a clinical syndrome that manifests as an abrupt impairment of kidney function. AKI is common in critically ill pediatric patients admitted to the pediatric intensive care units. AKI is a deleterious complication in critically ill children as it is associated with increased morbidity and mortality. This review provides an overview of the incidence, morbidity, and mortality of AKI in critically ill children in general and specific cohorts such as post-cardiac surgeries, sepsis, critically ill neonates, and post stem cell transplantation.